Traditional Chinese Medicine Oral Liquids Combined With Azithromycin for Mycoplasma pneumoniae Pneumonia in Children: A Bayesian Network Meta-Analysis - Chen, Zhe; Shi, Qingyang; Peng, Yingying; Chen, Yongjie; Cao, Lujia; Pang, Bo; Ji, Zhaochen; Liu, Chunxiang; Zhang, Junhua (Frontiers in Pharmacology, 2021)
Background:Mycoplasma pneumoniae pneumonia (MPP) causes flu-like symptoms in children, increasing the burden on the health and education systems. In China, traditional Chinese medicine oral liquids (TCMOLs) combined with azithromycin (TCMOLs + Azithromycin) is commonly used to treat MPP in children. However, TCMOLs with the optimal clinical applicability remain unknown. Here, we evaluated the clinical effectiveness and safety of TCMOLs + Azithromycin in children with MPP. Methods: We searched PubMed, Embase, Cochrane Library, Ovid, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform, and VIP information resource integration service platform databases for eligible randomized controlled trials (RCTs) published from database inception to October 2020. Two reviewers independently performed data extraction and risk of bias assessment. After Bayesian random effect modeling and surface under the cumulative ranking curve (SUCRA) scoring, we ranked each intervention. We assessed heterogeneity using multivariate meta-regression for potential modifiers and used the Grading of Recommendations, Assessment, Development, and Evaluation to rate pooled evidence’s certainty. Results: In the 63 included RCTs with 6,410 children, five different TCMOLs were combined with azithromycin. TCMOLs + Azithromycin had significantly better primary outcomes than did azithromycin alone. Of all TCMOLs, Xiaoer Xiaoji Zhike (XEXJZK)+Azithromycin showed the best effectiveness with respect to the response rate (odds ratio [OR] = 6.5, 95% credible interval [CrI] = 4.3–10; low certainty) and pulmonary rales disappearance time (mean difference [MD] = −2.1, 95% CrI: −2.9 to −1.2; low certainty) with SUCRA 85 and 80%, respectively. Pudilan Xiaoyan + Azithromycin showed the highest effectiveness with respect to cough disappearance time (MD = −2.6, 95% CrI: −3.4 to −1.7; very low certainty) and fever disappearance time (MD = −1.8, 95% CrI: −2.3 to −1.3; very low certainty) with SUCRA 87 and 87%, respectively. The difference in the adverse effects between TCMOLs + Azithromycin and azithromycin alone was nonsignificant. Conclusion: Of the different TCMOLs, XEXJZK may be the best option to combine with azithromycin to treat children with MPP. However, our results should be interpreted with caution due to the low certainty of evidence. In general, TCMOLs’ safety remains unclear because of a lack of evidence. More high-quality RCTs are needed to further evaluate efficacy and safety of these TCMOLs.